Exploring the Influence of Work-Life Balance and Perceived Organizational Support on Employee Engagement: Job Satisfaction as a Mediator Among Millennials - Primayani, Risa Rizki; Rivai, Harif Amali; Lukito, Hendra (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of work life balance and perceived organizational support on employee engagement, with job satisfaction as a mediating variable, among Millennial employees at PT Semen Padang. The research employed a quantitative approach with an explanatory research design. Data were collected through an online survey distributed via Google Forms to 221 respondents. The data were analyzed using Partial Least Square – Structural Equation Modelling (PLS-SEM). The results indicate that work life balance has a positive and significant effect on both employee engagement and job satisfaction. Perceived organizational support does not have a direct effect on employee engagement but has a positive and significant effect on job satisfaction. Furthermore, job satisfaction significantly influences employee engagement and mediates the relationships between work life balance and employee engagement, as well as between perceived organizational support and employee engagement.